Pengaruh Model Pembelajaran Role Playing Terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Lae Parira Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to determine whether the Role Playing learning model can increase interest in learning about Christian Religious Education and Characteristics of class VIII students at SMP Negeri 1 Lae Parira for the 2023/2024 academic year. The research method is descriptive quantitative. The population is all class VIII students of SMP Negeri 1 Lae Parira Dairi Regency for the 2023/2024 academic year, totaling 171 people and a sample of 43 people was determined, namely 25% of the total population using probability sampling techniques. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Role Playing learning model on interest in learning Christian Religious Education and Characteristics of class VIII students of SMP Negeri 1 Lae Parira for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) test a positive relationship obtained rxy value = 0.576 > rtable(a=0.05,n=43) = 0.301. b) Testing a significant relationship obtained tcount= 4.513 > ttable(a=0.05,dk=n-2=41)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=